Kinetics of CO2 absorption in aqueous blends of N, N-diethylethanolamine (DEEA) and N-methyl-1, 3-propane-diamine (MAPA). (16th June 2015) - Monteiro, Juliana G.M.-S.; Majeed, Hammad; Knuutila, Hanna; Svendsen, Hallvard F.
Abstract: This work presents experimental data on the CO2 transfer into aqueous blends of N, N -diethylethanolamine (DEEA) and N -methyl-1, 3-propane-diamine (MAPA). Additionally, data on density, viscosity and N2 O solubility into the studied blends are given. The data are interpreted using the two-film theory and invoking the pseudo-first order assumption. The DEEA clustering hypothesis allows for qualitatively explaining the complex behavior that is obtained in the experiments. The observed kinetic constant was modeled using the direct mechanism, considering water, MAPA and DEEA as possible proton receivers. The contribution of DEEA represents 52 to 98% of the observed kinetic constant. The empirical correlations for describing the observed kinetic constant presented in this work can be used, together with the physical properties given in this work, to predict the CO2 absorption flux into the studied DEEA/MAPA blends with reasonable accuracy. Highlights: Phase-change solvent system kinetics studied Potential for reduced CO2 capture energy penalty Aqueous blends of DEEA and MAPA form 2 liquid phases upon CO2 loading Kinetic data on CO2 absorption by DEEA/MAPA blends measured The DEEA clustering hypothesis qualitatively explains the observed data